Examination of Social Behavior and Cognition in Clownfish (Amphiprion ocellaris): Relationship to Artificial Rearing of Juveniles - Guodong Wang; Jixiang Liu; Jifang Yang; Song Ma; Zi Wang; Yunlong He; Xiaohan Li; Wenhui Yin; Xinyu Li; Jiahao Li; Kefeng Xu; Chong Wang; et al. (Fishes, 2025)
The overexploitation of wild populations for the marine ornamental trade necessitates optimized captive breeding, particularly for iconic species like the clownfish Amphiprion ocellaris. This study investigated the social behavior and cognitive abilities of juvenile clownfish in relation to artificial rearing practices. Using modified three-tank tests, we assessed social preference and cognition ability in two size groups: Small-bodied Group (SG: 2.0–2.5 cm) and Large-bodied Group (LG: 3.5–4 cm). The results indicated that clownfish have the following: (a) Strong Social Preference: Both SG and LG exhibited significant preference for areas near conspecifics (SPI > 0), with SG showing significantly higher SPI values than LG. (b) Developmental Stage Differences: SG demonstrated a stronger tendency to cluster tightly near conspecifics. LG showed wider exploration patterns and greater movement. (c) Cognition Ability: SG showed renewed interest towards a novel fish after habituation to a familiar fish, while LG displayed a stronger preference for the familiar fish. These findings suggest that clownfish juveniles possess advanced sociality and basic cognition ability. Furthermore, the observed shift in social interaction preference with developmental stages informs optimal timing for grading practices to minimize artificial rearing stress. This study provides some behavioral insights for optimizing large-scale artificial rearing protocols for clownfish, reducing pressure on wild populations.